Dependence of efficiency of polyalkyl acrylate-based pour point depressants on composition of crude oil - Oleg A. Kazantsev; Ildar R. Arifullin; Aleksey A. Moikin; Alexey P. Sivokhin; Alexander S. Medzhibovsky; Denis M. Kamorin; Dmitry V. Orekhov; Alexander S. Simagin (Egyptian Journal of Petroleum)
Thirteen polyalkyl acrylate-based depressor additives with C16-C26 alkyl groups containing 0–30 mol% of various polar groups (amide, amine, ammonium, N-vinylpyrrolidone, oligo(ethylene glycol)) have been synthesized and tested in 18 crude oil samples of significantly different compositions. It has been shown that the dependences of the depressor effect on the additive concentration pass through maxima. An approach that predicts the degree of decrease in pour point of oil in the presence of polyalkyl acrylate additives depending on the content of paraffin and resin-asphaltene components was proposed for the first time. A polyalkyl acrylate with C16-20 alkyl groups proved to be the most versatile additive. However, polymers with different lengths of alkyl groups or containing polar groups are more effective for some oils.